Flexible labor: restructuring the American work force. - Clinton, Angela (Monthly Labor Review, 1997)
Many businesses are replacing directly hired people with purchases of services and are moving toward the hiring of contingent workers. Flexible work arrangements have been used as a way to meet fluctuations in demand for a company's product, to supplement absent staff, and to lower the cost of labor. Some studies indicate that firms purchase services to avoid unionism, whereas others name increased competition and profit maximization as factors. Further studies show that more firms are taking advantage of greater economies of scale achieved by service companies or their specialized skills. Employment trends, occupational employment trends, industry shifts in occupational employment, industry output, and inputs to production are discussed.